Antibiotic prophylaxis in flexible ureterorenoscopy with negative urine culture (2023)
Objective: To improve susceptibility profiles of nosocomial bacteria, identifying the difference between infectious complications in patients undergoing endoscopic flexible ureterolithotomy (fURS) with negative urine culture (UC) that received extended antibiotic prophylaxis (EP) compared with standard antibiotic prophylaxis (SP).Methodology: This is a retrospective, observational, analytical cohort study, comparing infectious complications between patients undergoing fURS with negative UC who received EP versus SP. We include patients with susccessfull fURS, 20-mm stones and complete information.Results: Overall, 10.3% of patients had complications, 7.2% of patients had postoperative urinary infection, 1.8% had upper urinary tract infection (UTI) and 1.4% had urinary sepsis. Lower UTI were significantly more likely in the extended prophylaxis group with 6.8% versus 2.7% (RR = 2.8; 95% CI: 1.10-7.37, p = 0.030). The risk of upper UTI and sepsis did not show significant differences. A total of 69% patients with postoperative infection had isolated multidrug-resistant bacteria (MDRB) in the UC, with a higher risk in patients with extended prophylaxis (RR = 3.1; 95% CI: 1.33-7.59, p = 0.009).Conclusions: Patients with negative UC who underwent fURS using extended prophylaxis have two times higher risk of low UTI than patients with standard prophylaxis, without differences in the incidence of upper UTI or urinary sepsis. The risk of MDRB isolation in the postoperative UC is higher in the extended prophylaxis group, therefore we recommend the standard 60-min preoperative prophylaxis.Keywords: antibiotics; bacteria; infections; sepsis; urolithiasis.